WAYS TO RAISE THE QUALITY OF PEDAGOGICAL AND PSYCHOLOGICAL THESES - Nikolay V. Baryshnikov (Высшее образование в России)
Within the context of discussion a topical problem concerning modernization of a system of faculty certification the article presents the experience of Pyatigorsk State Linguistic University. The ways of interaction between the university administration and thesis committees, measures for raising the quality of pedagogical and psychological theses, and for raising the efficiency and transparency of thesis committees activities are viewed.